Relationship Between Pneumonia and Dysphagia in Patients With Multiple System Atrophy - Wada, Ayako; Kawakami, Michiyuki; Yamada, Yuka; Kaji, Kentaro; Hijikata, Nanako; Liu, Fumio; Otsuka, Tomoyoshi; Tsuji, Tetsuya (Frontiers in Neurology, 2022)
Introduction Dysphagia is one of the most clinically significant disabilities in patients with multiple system atrophy (MSA), because it can cause aspiration pneumonia, which is potentially fatal. In this study, the Neuromuscular disease Swallowing Status Scale (NdSSS), which was developed to evaluate dysphagia in patients with neuromuscular diseases, was used to evaluate patients with MSA. In addition, correlation between a history of pneumonia and swallowing function was evaluated. Methods Study 1: Reliability, concurrent validity, and responsiveness of the NdSSS in patients with MSA. In 81 patients for whom evaluation items could be collected, the NdSSS was tested for its interrater and intrarater reliability using weighted kappa statistics. Concurrent validity was assessed by correlating the NdSSS with existing scales (Functional Oral Intake Scale (FOIS), Functional Intake LEVEL Scale (FILS), and the unified MSA rating scale (UMSARS)) using Spearman's rank correlation coefficients. Sixty-three patients were evaluated by videofluorographic (VF) swallowing examination. To evaluate concurrent validity, Spearman's rank correlation coefficients were calculated between the NdSSS and VF swallowing assessments. Additionally, scale responsiveness was determined using the standardized response mean (SRM) in 23 patients who could be followed up to assess their long-term course. Study 2: Cross-sectional survey of swallowing function and history of pneumonia. Data regarding history of pneumonia, UMSARS, NdSSS, age, sex, MSA subtype, and disease duration were retrospectively obtained from the medical records of 113 patients with MSA. Differences in these parameters and NdSSS stage between those with and without a history of pneumonia were examined using the Mann-Whitney test or chi-squared test. Furthermore, clinical factors related to a history of pneumonia were examined by binomial logistic regression analysis. Results The NdSSS showed satisfactory reliability, concurrent validity, and responsiveness. A history of pneumonia was related to the severity of MSA, age, MSA subtype, and NdSSS stage. Binomial logistic regression analysis showed that NdSSS stage (odds ratio (OR), 0.490; 95% confidence interval (CI), 0.301–0.797, p = 0.001) and MSA subtype (OR, 4.031; 95% CI, 1.225–13.269, p = 0.021) were significantly associated with a history of pneumonia. Conclusions In patients with MSA, the NdSSS has sufficient reliability, concurrent validity, and responsiveness for assessing dysphagia. Patients with a history of pneumonia have more severe dysphagia. We found that the pneumonia risk was related to NdSSS stage and MSA-p (predominantly parkinsonism). Meticulous care to prevent aspiration is needed from early stages of the disease.